Basement shear zones development and shortening kinematics in the Ecrins Massif, Western Alps. Issue 2 (15th February 2014) - Bellanger, M.; Bellahsen, N.; Jolivet, L.; Baudin, T.; Augier, R.; Boutoux, A.
Abstract In the Western Alps, Oligocene shortening affected a highly heterogeneous European crust with Liassic half‐grabens inherited from the rifting stage and the finite deformation was strongly partitioned between the rigid basement and the weak Jurassic sediments. In the Ecrins Massif (Oisans, external crystalline massifs), where the half‐grabens are best exposed and preserved, compressional structures within the basement have to date never been described in details. This massif was shortened under moderate metamorphic conditions (250–350°C and 0.1–0.5 GPa), and the rheological contrast between the basement and the cover is strong. While the sediments are intensely folded, the cover‐basement interface presents apparent open folds underlined by the Lower Triassic layers. The basement itself shows a more localized deformation along several brittle‐ductile shear zones. We here report new evidences of such brittle‐ductile shear zones characterized by anastomosed phyllonitic shear bands rich in phengite and quartz, a low‐strength material where strain has localized. New detailed maps of reverse shear zones, faults, schistosity, and stretching lineations in both the cover and the basement are provided. We show that the Oligocene crustal shortening was mainly E‐W to ENE‐WSW. Local N‐S to NW‐SE shortening occurred and was limited to the eastern border of the Ecrins Massif, around the Penninic Frontal Thrust, which likely was a sinistral transpressive structure in this area. Finally, new balanced cross sections show that these basement shear zones have accommodated more than 50% of the Oligocene crustal shortening.